1998
DOI: 10.1016/s0006-3495(98)77711-2
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Chain Ordering on the Selectivity of Dipalmitoylphosphatidylcholine Bilayer Membranes for Permeant Size and Shape

Abstract: The effects of lipid chain packing and permeant size and shape on permeability across lipid bilayers have been investigated in gel and liquid crystalline dipalmitoylphosphatidylcholine (DPPC) bilayers by a combined NMR line-broadening/dynamic light scattering method using seven short-chain monocarboxylic acids (formic acid, acetic acid, propionic acid, butyric acid, valeric acid, isovaleric acid, and trimethylacetic acid) as permeants. The experimental permeability coefficients are compared with the prediction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
165
0
2

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(178 citation statements)
references
References 76 publications
(99 reference statements)
9
165
0
2
Order By: Relevance
“…We note, however, that the trend is not entirely without precedent; the gel-phase dipalmitolyphosphatidylcholine (DPPC) studies of Xiang and Anderson (14,16,17) also found a decreasing permeation coefficient from acetic to propionic acid, but for larger acids P increased again (17). DPPC is a fully saturated lipid, thus P values are orders of magnitude smaller in the gel phase (17) and so are easier to measure accurately. In constrast, soy lecithin remains in the fluid phase from 3°C to 80°C, because of the high proportion of unsaturated lipids (40).…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…We note, however, that the trend is not entirely without precedent; the gel-phase dipalmitolyphosphatidylcholine (DPPC) studies of Xiang and Anderson (14,16,17) also found a decreasing permeation coefficient from acetic to propionic acid, but for larger acids P increased again (17). DPPC is a fully saturated lipid, thus P values are orders of magnitude smaller in the gel phase (17) and so are easier to measure accurately. In constrast, soy lecithin remains in the fluid phase from 3°C to 80°C, because of the high proportion of unsaturated lipids (40).…”
Section: Resultsmentioning
confidence: 77%
“…On the other hand, some weak acid protonophores may also exert detrimental effects on cellular processes such as oxidative phosphorylation, apoptosis (7), and photosynthesis (8). The transport of weak acids across model cell membranes and the determination of permeation rates have consequently been the subject of a considerable number of studies (9)(10)(11)(12)(13)(14)(15)(16)(17)). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The permeability of a given compound reflects its partition coefficient into the barrier domain, PC barrier/water , and its diffusion coefficient within the barrier, D barrier , as described below 10) where d is the thickness of the barrier. In both bulk solvents (16) and lipid bilayers (17), the diffusion coefficient varies inversely with the minimum crosssectional area of the permeant (ie, D barrier ∝ [molecular volume] 2/3 ). Figure 5 shows the minimum cross-sectional area view for each compound in the series of p-methylhippuric acids, along with the relative surface area normalized to that of the unsubstituted p-methylhippuric acid.…”
Section: Functional Group Contributions To the Standard Free Energy Omentioning
confidence: 99%
“…This is the reason of the non-planar spaces between crystalline lipid lamellae and their adjacent cells outer membrane. Fluid lipids in skin barrier are crucially important for transepidermal diffusion of the lipidic and amphiphilic molecules, occupying those spaces for the insertion and migration through intercellular lipid layers of such molecules [59,60]. The hydrophilic molecules diffuse predominantly "laterally" along surfaces of the less abundant, water filled inter-lamellar spaces or through such volumes; polar molecules can also use the free space between a lamella and a corneocyte outer membrane to the same end [61].…”
Section: Routes Of Drug Penetration Through the Skinmentioning
confidence: 99%